DIGITAL MARKETING STRATEGY INTEGRATION: AN ANALYSIS OF SOCIAL MEDIA MARKETING AND CONTENT MARKETING ON WILLINGNESS TO PAY A PREMIUM PRICE IN THE INDONESIAN E-SPORTS EQUIPMENT INDUSTRY - Shelvy Kurniawan; Stevando Magara Haposan Sihombing (Pedagogic Research-Applied Literacy Journal, 2026)
This study aims to analyze the influence of Social Media Marketing and Content Marketing on Brand Awareness and its impact on Willingness to Pay a Premium Price among e-sports equipment consumers in Indonesia. The rapid growth of the e-sports industry requires companies to have effective digital marketing strategies to build strong brand value amidst market competition. The research method used is a quantitative approach. Data collection was carried out by distributing questionnaires to e-sports equipment consumers in Indonesia. The data analysis technique used is Structural Equation Modeling (SEM) based on Partial Least Square (PLS) with the help of SmartPLS 4.0 software. The results showed that: (1) Brand Awareness has a significant and positive effect on Willingness to Pay a Premium Price; (2) Content Marketing has a significant and positive effect on Brand Awareness; (3) Content Marketing has a significant and positive effect on Willingness to Pay a Premium Price; (4) Social Media Marketing has a significant and positive effect on Brand Awareness and (5) Social Media Marketing has a significant and positive effect on Willingness to Pay a Premium Price. These findings indicate that the use of the latest trends on social media and the provision of in-depth content regarding the technical specifications of e-sports equipment can create a top-of-mind position for consumers. This ultimately encourages consumers' willingness to pay a higher price even though there are competitor products with similar features. This study provides recommendations for marketing practitioners to focus on the relevance of digital content to maintain a competitive advantage in the premium market segment.